THE ESTIMATION OF SPATIAL GENETIC DIVERSITY OF VENDACE (COREGONUS ALBULA L.) POPULATIONS IN BALTIC LAKELAND (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The vendace (Coregonus albula) is native widespread to lakes in northern Eurasia. In the Baltic Lakeland region, populations of local whitefish are the remnants of the Arctic freshwater faunal complex and often regarded as an example of a glacial relict and indicator species of the state of the lake ecosystem. Together with other whitefishes vendace belongs to economically valuable fish species.; The territory of the Baltic Lakeland region is located on the territory of three countries (Latvia, Lithuania and Belarus). The range of the vendace population is declining in waterbodies in Latvia and Belarus, the catch is insignificant and unstable, and this species is included in the list of specially protected fish species. However, in Lithuania this species is widespread and not protected.; The understanding fish population genetic diversity is very important for protection of rare communities and conservation of unique native populations. The estimation of the genetic structure of populations and determining the causes of genetic differentiation and the factors that promote variation between and within populations is fundamental for understanding adaptation and is, therefore, a primary goal of population and conservation genetics. Little is known about the genetic structure of vendace populations in waterbodies in Baltic Lakeland.; In this study eight microsatellite loci were used to investigate the genetic structure within and between populations in six vendace populations from Baltic Lakeland, namely Drivyaty, Rudakova, Strusto, Snudi, Naroch and Drūkšiai. Allelic variation was different in all investigated vendace populations; the observed and expected heterozygosity level was quite high. Bayesian-based STRUCTURE analysis suggested that there are two main genetic groups within our study area, separating Rudakova, Naroch and Strusto into one and others studied populations into the other cluster. These populations would be differentiated due to drift, reduced gene flow and possibly selection that promoting divergence. ; ;